Interactions of arsenic and phosphorus in their uptake and transportation in plants: Advances and prospective research on the mechanisms and approaches for alleviating arsenic stress - Ameer Khan; Farah Kanwal; Muhammad Shahzad; Shama Naz; Sanaullah Jalil; Guoping Zhang (Journal of Integrative Agriculture, 2025)
Metalloid arsenic (As) is not a necessary element for plants, but its excessive accumulation is toxic to plants, and it also poses a great health risk to humans via the food chain. Plants absorb and metabolize As through a variety of processes. Arsenate in the form of As5+ is absorbed by phosphate transporters, but methylated As and As3+ enter plant tissues mainly through aquaporin channels. Various strategies and practices have been proposed and applied to alleviate As toxicity or reduce As accumulation in plants, but an efficient and environment-friendly approach has yet to be developed. This review comprehensively explores As sources and uptake mechanisms, as well as the interactions of phosphorus (P) and As in their uptake, transportation and influences on plant growth and physiological activities. This comprehensive review covers the transport, metabolism, and tolerance processes that plants exhibit in response to As stress and the addition of P. In addition, we also present recent advances in reducing As toxicity and accumulation by improving P nutrition, manipulating P transporter genes and optimizing the plant microbial community. Finally, the future research directions and main challenges are briefly discussed.